2019
DOI: 10.2218/finsoc.v5i1.3016
|View full text |Cite
|
Sign up to set email alerts
|

Why performativity limits credit rating reform

Abstract: The 2008 crisis made clear that credit rating agencies (CRAs) can contribute to systemic financial risk. Surprisingly, post-crisis reforms have hardly addressed the underlying problems, including rating agencies’ methodologies, their ratings’ homogeneity, and widespread market reliance on these signals. Current scholarship on CRA regulation blames policymakers’ unwillingness to fix systemic problems. This article draws on insights from the social studies of finance literature to provide a different explanation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…These entangled cognitive processes at the personal level will expand to the extent that they affect the economy as a whole. The study on the combination of herding effect and default risk can also be found in the literature Ma et al (2018), Stellinga (2019), Albu et al (2019).…”
Section: Introductionmentioning
confidence: 94%
“…These entangled cognitive processes at the personal level will expand to the extent that they affect the economy as a whole. The study on the combination of herding effect and default risk can also be found in the literature Ma et al (2018), Stellinga (2019), Albu et al (2019).…”
Section: Introductionmentioning
confidence: 94%
“…But this has become less and less the case over the past decades as imbalances have accumulated, the probability of shocks has grown and shock-absorbing capacities have declined. After decades of relative calm, 50 Stellinga and Mügge (2017); Stellinga (2018Stellinga ( , 2019 51 Bonds issued by governments deemed reliable are exceptions. Safe havens in times of crisis, they can rise in value.…”
Section: Systemic Instabilitymentioning
confidence: 99%
“…Another way that the concept has been put to work is in understanding the difficulties faced by regulators. In a series of articles addressing post-crisis developments from credit rating reform to macroprudential policies, Stellinga (2019Stellinga ( , 2020Stellinga & Mügge, 2017) argues that while regulators don't think expressly in terms of performativity, they do recognize that markets have reflexive, adaptive, and complex dynamics which militate against attempts at market control. From this perspective, it is not necessary to see regulators as captured or ideologically aligned with financial interests to explain their timidity.…”
Section: Lesson 2: Models Mattermentioning
confidence: 99%